Analysis of mammalian gene batteries reveals both stable ancestral cores and highly dynamic regulatory sequences - Ettwiller, Laurence; Wittbrodt, Joachim (Genome biology, 2008)
Changes in gene regulation are suspected to comprise one of the driving forces for evolution. To address the extent of cis-regulatory changes and how they impact on gene regulatory networks across eukaryotes, we systematically analyzed the evolutionary dynamics of target gene batteries controlled by 16 different transcription factors.
Gesehen am 17.05.2017